2014
DOI: 10.3109/13651501.2014.940054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylphenidate treatment on appetite and levels of leptin, ghrelin, adiponectin, and brain-derived neurotrophic factor in children and adolescents with attention deficit and hyperactivity disorder

Abstract: Leptin and BDNF were not associated with poor appetite and/or weight loss due to methylphenidate treatment. However, ghrelin and adiponectin might be biomolecules that play a role in underlying neurobiological mechanisms of methylphenidate-related appetite or weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 47 publications
3
16
0
4
Order By: Relevance
“…14,15 Indeed, loss-of-appetite is among the most commonly reported side effects in ADHD patients receiving pharmacotherapies such as MP-a response that is often attributed to nausea. 16,17 However, it is important to emphasize the large variation in responsiveness to MP and in its side-effect profile, factors which highlight the importance of identifying individual-difference factors that moderate the consequences of these drugs. For example, in an earlier study, our group found that in response to a single-dose MP challenge, mean snack-food consumption and appetite ratings decreased from the placebo to the drug condition in all groups of participants in the 2 (normal weight vs. obese) 3 2 (men vs. women) design matrix except in the obese men who showed no differences between the two conditions.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Indeed, loss-of-appetite is among the most commonly reported side effects in ADHD patients receiving pharmacotherapies such as MP-a response that is often attributed to nausea. 16,17 However, it is important to emphasize the large variation in responsiveness to MP and in its side-effect profile, factors which highlight the importance of identifying individual-difference factors that moderate the consequences of these drugs. For example, in an earlier study, our group found that in response to a single-dose MP challenge, mean snack-food consumption and appetite ratings decreased from the placebo to the drug condition in all groups of participants in the 2 (normal weight vs. obese) 3 2 (men vs. women) design matrix except in the obese men who showed no differences between the two conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Alınan örnekler oda sıcaklığında 10 dakika 3000 devirde santrifüj edilerek plazmaları ayrıldıktan sonra analiz edilinceye kadar -80˚C'de saklandı. Grelinin beyinde dopaminerjik yolakları etkileyerek DEHB'nin dikkatsizlik ve hiperaktivite belirtileri ile ilişkisinin olabileceği ve MPH ile ilişkili iştah azlığı ve kilo kaybının altında yatan nöro-biyolojik düzenekle ilişkilendirilmesine rağ-men, 16,33 grelin ve DEHB ilişkisi hakkında az sayıda çalışma vardır. Bir çalışmada 6-12 yaşları arasındaki 33 erkek çocukta tedavi öncesi ve iki aylık tedavi sonrası grelin düzeyleri ölçülmüş, tedavi öncesi ve sonrası grelin düzeyleri arasın-da fark olmadığı belirtilmiştir.…”
Section: Npy Leptin Ve Grelin Düzeylerinin Değerlen-dirilmesiunclassified
“…18 Diğer bir çalış-mada MPH tedavisi öncesi DEHB grubu ile sağlıklı kontrol grubu arasında grelin düzeyleri arasında fark olmadığı, iki aylık MPH tedavi sonrasında grelin düzeylerinin arttığı saptanmıştır. 16 Bununla birlikte diğer çalışmalardan farklı olarak, bir çalışmada tedavi öncesi DEHB grubunda kontrol grubuna göre grelin düzeyinin anlamlı olarak yüksek olduğu da bildirilmiştir. 17 Aynı çalışmada üç aylık MPH tedavisi sonrası grelin düzeyinin tedavi öncesine göre anlamlı oranda düştüğü bulunmuştur.…”
Section: Npy Leptin Ve Grelin Düzeylerinin Değerlen-dirilmesiunclassified
See 2 more Smart Citations